Association of Telescopic Rod and Ilizarov Frame in Fibular Hemimelia Surgical Treatment - Ulici, Al.; Popescu, M. B.; Ladaru, A. B. (International Journal of Orthopedics and Rehabilitation, 2016)
Fibular hemimelia is a rare congenital malformation, but one of the most common long-bone length deficiencies, without a clearly known cause. It can occur as an isolated anomaly or as part of a malformation syndrome. The presentation may vary from mild fibular hypoplasia to fibular absence. We reviewed the case of a 4 year old male who referred to our clinic at the age of one year, presenting with leg length discrepancy, bowed leg and with an absence of the peroneal malleolus, the fifth toe and equinovalgus deformity. After further investigations and presenting the family the treatment options, they ruled out amputation and surgical treatment was started with two circumferential periosteal releases followed by a telescopic rod implant and an Ilizarov frame fixator. The purpose of the present report is to highlight the good outcomes of combining the telescopic rod and Ilizarov frame fixator in complete fibular hemimelia.